Determinants Factors of Interest Rates on Three-Month Deposits of Bank Persero - Kurniawan, Tedy; Prajanti, Sucihatiningsih Dian Wisika (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
This research aims at analyzing the influence of Capital Adequacy Ratio (CAR), Operating Expenses of Operating Income (BOPO), inflation, exchange rate, and the amount of money supply (M1) to the interest rate of three month deposits of the State-Owned Bank in Indonesia in 2007-2015. This research uses the error correction model analysis. The result obtained is the CAR that has a significant effect on the long term and has no effect on the short term, BOPO has a significant influence on the long term and short term, inflation has the significant effect on the long term and has no effect on the short term, the exchange rate has an influence on the short and long term, the money supply has no effects on the short and long-term on the interest rate on three month deposits of the State-Owned Bank.